2021
DOI: 10.3390/molecules26237128
|View full text |Cite
|
Sign up to set email alerts
|

Fermented Oyster Extract Attenuated Dexamethasone-Induced Muscle Atrophy by Decreasing Oxidative Stress

Abstract: It is well known that oxidative stress induces muscle atrophy, which decreases with the activation of Nrf2/HO-1. Fermented oyster extracts (FO), rich in γ-aminobutyric acid (GABA) and lactate, have shown antioxidative effects. We evaluated whether FO decreased oxidative stress by upregulating Nrf2/HO-1 and whether it decreased NF-κB, leading to decreased IL-6 and TNF-α. Decreased oxidative stress led to the downregulation of Cbl-b ubiquitin ligase, which increased IGF-1 and decreased FoxO3, atrogin1, and Murf1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
(91 reference statements)
0
13
0
Order By: Relevance
“…The placebo capsule was identical to the FSO capsule in appearance and was filled with dextrin. In a previous animal study, no toxicity was observed with 100 mg/kg and 200 mg/kg admission of FSO for 28 days [ 14 ]. Therefore, a safe and effective dose of 200 mg/kg was converted to the dose appropriate for a 60 kg adult human based on the body surface area and was calculated as 960 mg/day.…”
Section: Methodsmentioning
confidence: 99%
“…The placebo capsule was identical to the FSO capsule in appearance and was filled with dextrin. In a previous animal study, no toxicity was observed with 100 mg/kg and 200 mg/kg admission of FSO for 28 days [ 14 ]. Therefore, a safe and effective dose of 200 mg/kg was converted to the dose appropriate for a 60 kg adult human based on the body surface area and was calculated as 960 mg/day.…”
Section: Methodsmentioning
confidence: 99%
“…For example, ROS have been demonstrated to promote muscle atrophy by activating the ubiquitin‐proteasome pathway [23]. The pathological changes in skeletal muscle atrophy can be prevented by decreasing ROS production [24]. Dihydroethidium staining showed that the ROS content was significantly increased in the skeletal muscle of the MA group compared to that in the CON group, whereas exercise significantly decreased the high ROS levels associated with aging (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The placebo was identical to the FO capsule in appearance and was filled with corn starch. Based on the results of a previous animal study, which showed that the minimum efficacious and safe dose of FO was 200 mg/kg ( 10 ), the dose used in the animal subjects was converted to a human equivalent dose based on the person’s body surface area, i.e., 960 mg for individuals weighing 60 kg. In addition, a previous preliminary clinical study had established the safety of FO extracts at 1,000 mg/day ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the effects of lactic acid-fermented oyster extract (FO) containing GABA and lactic acid, produced by lactic acid fermentation of oysters, on bone formation ( 7 ), height growth ( 8 ), and exercise performance improvement ( 9 ) have been reported. Also, a previous study showed that GABA-enriched FO reduced muscle proteolysis by increasing mRNA levels of IGF-1 expression in dexamethasone-treated animals ( 10 ). These data suggest that GABA is a potent bioactive compound for improving muscle health ( 11 ).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation